2022
DOI: 10.1039/d1em00497b
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative potential of fresh and aged elemental carbon-containing airborne particles: a review

Abstract: Elemental carbon is often found in ambient particulate matter (PM), and it contributes to PM's oxidative potential (OP) and thus poses great health concerns. Previous review articles mainly focused on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 179 publications
0
15
0
Order By: Relevance
“…83,84 Besides, it shows great significance in regulating the oxidative potential of atmospherically relevant carbon matter. 85,86 In our early study, we revealed the important role of redox-active organics containing quinone functional groups in triggering fast SO 2 oxidation mediated by the photosensitized reaction using model compounds. 68 The reaction mechanism of the multiphase photosensitized SO 2 oxidation where HULIS molecules are involved is described in Figure 2e.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…83,84 Besides, it shows great significance in regulating the oxidative potential of atmospherically relevant carbon matter. 85,86 In our early study, we revealed the important role of redox-active organics containing quinone functional groups in triggering fast SO 2 oxidation mediated by the photosensitized reaction using model compounds. 68 The reaction mechanism of the multiphase photosensitized SO 2 oxidation where HULIS molecules are involved is described in Figure 2e.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We hypothesize that the enhanced sulfate formation in aged particles may be related to the large amounts of secondary oxidants, possibly reactive oxygen species (ROS), formed under light and air, as no sulfate can be found in aged IS–NaCl under dark conditions. ROS are highly reactive in the atmosphere; they include free radicals (e.g., OH • , HO 2 • , and RO 2 • ), ions (e.g., O 2 – , ClO – , and ONOO – ), and peroxides (e.g., ROOH and ROOR’).…”
Section: Resultsmentioning
confidence: 99%
“…For example, black carbon and soot particles produce active intermediates (Y. Y. Liu & Chan, 2022;Zhu et al, 2020), which may interact with 𝐴𝐴 CO3 .− and have some impact on the reaction mechanism considered here. Additionally, atmospheric NO x (NO + NO 2 ) is one of the pollutant gases that are prone to be involved in the dust-driven SO 2 oxidation process (He et al, 2014;Qu et al, 2016).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…should be considered in future work in a better understanding of the effect of carbonate radical ions on SO 2 oxidation. For example, black carbon and soot particles produce active intermediates (Y. Y. Liu & Chan, 2022; P. Zhang et al., 2022; Zhu et al., 2020), which may interact with normalCO3. ${\mathrm{C}{\mathrm{O}}_{3}}^{.-}$ and have some impact on the reaction mechanism considered here. Additionally, atmospheric NO x (NO + NO 2 ) is one of the pollutant gases that are prone to be involved in the dust‐driven SO 2 oxidation process (He et al., 2014; Qu et al., 2016).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%